An investigation into appreciation in “perfect spy” by larry berman and its vietnamese version “điệp viên hoàn hảo” by đỗ hùng in perspectives of appraisal theory and functional grammar (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis aims to investigate the appreciation used in “Perfect Spy” by Larry Berman and its Vietnamese version “Điệp Viên Hoàn Hảo” by Đỗ Hùng with the objectives of presenting, describing and analysing the evaluative language under the representations of syntactic features in view of Functional Grammar and semantic features in view of Appraisal framework. This contrastive study was conducted with a combination of qualitative and quantitative method. Within 100 samples of appreciation collected from Larry Berman's work and those from Đỗ Hùng's translational version, the researcher attempted to focus on appreciation of simple, compound, compound-complex sentences in Clause as message and exchange; Nominal group. For semantic features, three types were examined: reaction, composition and valuation in positive and negative forms. With each area, this thesis discovers the similarities as well as differences in linguistic realizations of appreciation in the two languages. Last but not least, some implications for English language teaching and translating would be put forward. The study found that it might be advisable that teachers, leaners and translators should be equipped with not only sentence structures and nominal groups but semantic forms of reaction, composition and valuation as well so that they can show a set of evaluations of products, processes and entities both positive and negative meaning more effectively and persuasively.